سائنس کے ترقی یافتہ مصنوعی گوشت کا فقہی جائزہ : A JURISPRUDENTIAL REVIEW OF SCIENCE-ADVANCED SYNTHETIC MEAT - Syed Hayatullah; Anjum Riaz; Fozia Yaseen (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
We see the development of science and technology in every field of life. Such as Food Science is getting advances in food development but for Muslims the issue of Halal and Haram has been raised as well. Manufacturing of synthetic meat is a current issue. In this article, the opinions of the Islamic Jurists have been explained. Synthetic meat is considered Halal after fulfilling a few conditions that are; 1) the muscle tissues must not be taken from a part of animal which, after removal, may still be alive, as that part will be considered dead. 2) the dead part of body of an animal, even halal animal, is not Halal. 3) if the halal part has been mixed up with a haram ingredient, which cannot be separated from it, is considered haram. synthetic meat must not be harmful to human body. Failing any of the given conditions can harm the objectives of shariah. Especially the objective of protection of Deen and life cannot be achieved. While the Islamic Shariah insures protection of Deen, life, wealth, intellect, and race along with the development of human beings.